Spatial development of sports facilities in Hungarian cities of county rank - Kozma Gábor; Pénzes János; Molnár Ernő (Bulletin of Geography. Socio-Economic Series)
Nowadays more and more attention is devoted to the spatial development of the location of sports facilities within cities. The main aim of our paper is to observe the most important spatial characteristics of their development in Hungarian cities of county rank. In these cities three main periods of development of sports facilities can be observed. Larger sports facilities were constructed especially on the edge of cities or in the suburbs, while in the case of smaller facilities a bigger role was played by locations within the city boundaries. As regards the factors influencing the location of sports facilities, the most important role was played by the location of available land areas, besides accessibility and from the mid-1960s links to existing facilities can be mentioned as well.